1994
DOI: 10.1115/1.2901806
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Zirconium and Boron on Low Carbon Steel Weld Metal Microstructure

Abstract: By substituting zirconium-boron additions for titanium-boron additions in the weld deposit, further understanding of the role of specific microalloying additions on the suppression of grain boundary ferrite and the promotion of the intragranular formation of acicular ferrite in low carbon steel weld metal is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
7
0
4
Order By: Relevance
“…Previous research has shown that Ti-rich compounds are potent nucleants in cast ferritic steels, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and this is often attributed to lattice matching between {001} faces of both the compounds and ␦ -ferrite. [3,12,17] Other factors such as the topographical features of the nucleating surface, the chemical nature of the substrate, and the electrostatic potential between the two phases at the nucleating interface are also likely to be significant.…”
Section: Orientation Relationship Between Tin and ␦ -Ferritementioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown that Ti-rich compounds are potent nucleants in cast ferritic steels, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and this is often attributed to lattice matching between {001} faces of both the compounds and ␦ -ferrite. [3,12,17] Other factors such as the topographical features of the nucleating surface, the chemical nature of the substrate, and the electrostatic potential between the two phases at the nucleating interface are also likely to be significant.…”
Section: Orientation Relationship Between Tin and ␦ -Ferritementioning
confidence: 99%
“…[3,12,17] Other factors such as the topographical features of the nucleating surface, the chemical nature of the substrate, and the electrostatic potential between the two phases at the nucleating interface are also likely to be significant. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Despite the inherent experimental difficulties in determining a precise orientation relationship (OR) between TiN and ferrite [10] at the chill surface of a thin strip, such a relationship was estimated by EBSD. As TiN exhibits cubic crystal symmetry [17] and a particle face corresponds to {001} and the diagonals of each face to ͗011͘, experiments were carried out to relate the orientation of cuboidal particles on the strip surface to their its adjacent ferrite grain.…”
Section: Orientation Relationship Between Tin and ␦ -Ferritementioning
confidence: 99%
See 1 more Smart Citation
“…The welding of offshore structures, especially those found near the Arctic Circle, is delicate since it is important to obtain high toughness weldments at low temperature. High toughness in welds is generally proportional to the amount of acicular ferrite found in the microstructure ( Terashima & Hart, 1984; Abson & Pargeter, 1986; Dowling et al, 1986 ; Mills et al, 1987 ; Oh et al, 1990 ; Evans, 1996). Moreover, numerous authors have specified that inclusions, particularly specific phases on the surface of these inclusions, favour the formation of acicular ferrite ( Keville, 1983; Bhatti et al, 1984 ; Evans, 1986; Abson, 1989; Court & Pollard, 1989; Thewlis, 1989; Es‐Souni et al, 1991 ; St‐Laurent & L'Espérance, 1992a, b; Thewlis, 1994 ; Fox & Brothers, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to adding of manganese the authors of work [2] used additions of titanium and boron to the charge of flux-cored wire having obtained more than 90 % of AC in weld metal during welding in air, here the content of boron and titanium was in the limits of 0.004-0.008 . Predicted formation of structural components in wet underwater welding [1] at different depth and 0.04-0.08 %, respectively.…”
mentioning
confidence: 99%